1973
DOI: 10.1103/physrevb.8.3875
|View full text |Cite
|
Sign up to set email alerts
|

InterbandΓ6Γ8Magnetoabsorption in HgTe

Abstract: Magnetoabsorption associated with I 6 I, transitions was investigated at 4.4 K, on pure n-type HgTe thin crystals in the spectral region 300-400 meV for a and m polarizations. Analysis of experimental spectra is performed using both the three-band model (including the nonparabolicity), and the theory of Luttinger. Band parameters are determined by fitting transition energies:Er, -Er, = 302.5 meV, mr /mo =0028+0.00» and gr, = -41+4 at I I 8 Luttinger parameters (y, = -12.8, & =-8. 4, z =-10. 5) satisfactorily e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
8

Year Published

1974
1974
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(29 citation statements)
references
References 10 publications
2
19
0
8
Order By: Relevance
“…The energy corresponding to the state (A16) E,,(k,) and the coefficients C;, (k,) are, respectively, the eigenvalues and eigenvectors of a numerical, 4 x 4 matrix [27]. Using (AlG) and the definition Replacing the left-hand side of (A24) with the right-hand side of (A25) and inserting (A23) we obtain immediately This completes the proof of equation (7).…”
Section: (As')mentioning
confidence: 67%
See 1 more Smart Citation
“…The energy corresponding to the state (A16) E,,(k,) and the coefficients C;, (k,) are, respectively, the eigenvalues and eigenvectors of a numerical, 4 x 4 matrix [27]. Using (AlG) and the definition Replacing the left-hand side of (A24) with the right-hand side of (A25) and inserting (A23) we obtain immediately This completes the proof of equation (7).…”
Section: (As')mentioning
confidence: 67%
“…where n, k,, kz denote Landau quantum numbers, while cr accounts for the existence of four series of Landau levels (cr = &, b*) [27];…”
Section: (As')mentioning
confidence: 99%
“…В работе [19] показано, что этот уровень имеет оди-наковую природу в 2D и 3D системах, и в обозначениях Галднера и др. [20] его энергия может быть представлена следующим образом: [21]. Отметим, что зависимость от магнитного поля энергии одно-кoмпонентной волновой функции наинизшего уровня Ландау подзоны H1 в работе Криштопенко и др.…”
Section: характеристика образцовunclassified
“…In [17] it is shown that this level is of the same nature in two and in three dimensions and it is mapped on the b set level of Guldner et al [18] …”
Section: /(V·s)mentioning
confidence: 99%